Repeated Dientamoeba fragilis infections: a case report of two families from Sydney, Australia - Damien Stark; Joel Barratt; John Ellis; John Harkness; Deborah Marriott (MDPI AG, 2009)
We report cases of two unrelated families who both presented with recurrent Dienta-moeba fragilis infections. Subsequent antimicrobial therapy resulted in the clearance of D. fragilis and total resolution of gastrointestinal symptoms in both families. This report highlights the potentially recurrent nature of D. fragilis infections and the need for laboratories to routinely test for this organism.